Ao sul do Brasil oitocentista: escravidão e estrutura agrária em Caçapava 1821-1850 - Corrêa, André do Nascimento (2013)
This research is included in "History, Culture and Power", and "Integration, Politics and Frontier" studies of History master at UFSM. It is also linked with the project "Social Hierarchy, labour and family in the meridional border of Brasil". The purpose of this research is to analyze the socioeconomic characteristics from the people of Caçapava, in Rio Grande do Sul state, during the first half of the nineteenth century focusing on slave labour. The main sources are the post mortem inventories among 1821 and 1850. For this reason, a bibliographical dialogue about the studies of Agrarian History and slavery were accomplished. . In this debate, it is investigated some studies realized in the last years in order to discuss the crucial concepts of treatment concerning the resources of social and economic universe, which is also approached in this research. This discussion allowed us to understand some local peculiarities, for example, how the slave labor was used and the intensity of itself. In Addition, the analysis of documental sources show the existence of creole and African slaves revealing a connection with the transatlantic traffic, even though it was a region with cattle breeding predominance as in larger or as small scale besides being concentrated on the internal market. Likewise, most of the producers and slave owners were cattle breeders. Among them there was a large amount of land and animals for a few. However, there were a large number of small producers, many of them slave owners as well. Therefore, this research points to a social universe more complex than the ones usually portrayed in books related to the local context in this period.